Value of screening for nonalcoholic fatty liver disease in hyperuricemic patients with normal body mass index by two-dimensional ultrasound: Upper Egypt experience - Amro M Hassan; Mohammed H.A Elhaw; Ahmed Abd-Elrady Ahmed; Tarek M.M Mansour; Tarek M Abd-Elaziz; Mohamed Z.A Shoaeir (Wolters Kluwer Medknow Publications, 2020)
Background Nonalcoholic fatty liver disease (NAFLD) is major health problem, as it affects 20‑30% of the general population, and patients with NAFLD are at risk of progression toward liver cirrhosis and hepatocellular carcinoma and consequently lead to liver transplantation. NAFLD is strongly associated with obesity and metabolic syndrome, so NAFLD is usually seen in patients who have increased BMI, type 2 diabetes, and high cholesterol and triglycerides. Uric acid (UA) could play a role in pathogenesis of metabolic syndrome through oxidative stress and inflammatory response. Moreover, UA has been shown to promote lipid peroxidation, which could play a role in initiation and progression of NAFLD. Aim To evaluate the value of screening for NAFLD in hyperuricemic patients with normal BMI by two-dimensional ultrasound. Patients and methods This cross-section study was conducted on 100 persons: 50 patients diagnosed with hyperuricemia as the case group, and 50 persons with normal serum uric acid (SUA) who were crossed matched with the cases as a control group. Results This study showed that hyperuricemic patients had high rate of NAFLD (38%) more than people with normal SUA (20%), with P value was 0.025, and grade of NAFLD was higher in individuals with high SUA than individuals with normal SUA group, with P value was 0.048. Moreover, the levels of alanine aminotransferase, aspartate aminotransferase, and alkaline phosphatase were significantly increased in hyperuricemic patients more than individuals with normal UA level. Conclusions This study showed high rate of NAFLD among individuals with high SUA than individuals with normal SUA, and the ultrasound grading of NAFLD was higher in individuals with high SUA group than individuals with normal SUA.